Thermal mechanical coupling analysis of a flexible spoke non-pneumatic tire - Fu, Hongxun (Strojniški vestnik, 2022)
A new type of non-pneumatic tire with a flexible spoke structure is proposed to solve traditional pneumatic tire defects, such as easy bursting, the requirement of real-time maintenance to keep tire pressure, and a complex manufacturing process. The thermal mechanical coupling characteristics of the flexible spoke non-pneumatic tire are studied in detail to obtain the steady-state temperature field distribution pattern under different operating conditions. A unit configuration method is proposed to build the 3D model of the flexible spoke non-pneumatic tire. Then, the thermal-mechanical sequential coupling method is used to analyse the deformation, energy loss and heat conduction of the flexible spoke non-pneumatic tire. Finally, the steady-state temperature field distribution pattern under thermal-mechanical coupling is obtained. The results show that the high temperature region of the non-pneumatic tire is mainly distributed in the middle bending part of the flexible spoke unit, and the temperature gradually decreases from the centre of the flexible spoke to the surrounding parts. The influence of load on the temperature change of non-pneumatic tire is greater than that of the driving speed. This study provides a theoretical basis and method guidance for solving the failure problem of the non-pneumatic tires under the action of thermal-mechanical coupling.
Keywords: flexible spoke structure; metoda konfiguracije enot; nepnevmatska kolesa; non-pneumatic tires; numerična analiza; preizkus prototipa; temperature field; temperaturno polje; termomehanska sklopitev; thermal mechanical coupling; unit configuration method; upogljive napere